2021
DOI: 10.1039/d0na01061h
|View full text |Cite
|
Sign up to set email alerts
|

Continuous gas-phase synthesis of core–shell nanoparticles via surface segregation

Abstract: Synthesis methods of highly functional core@shell nanoparticles with high throughput and high purity are in great demand for applications, including catalysis and optoelectronics. Traditionally chemical synthesis has been widely explored,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 92 publications
2
31
0
2
Order By: Relevance
“…To demonstrate that the agglomeration is occurring on the fibers and not in the beam (as has been sometimes reported for this type of synthesis [ 47 , 48 ]), Figure 6 shows an SEM image of a lacy carbon TEM grid after passing the aerosol over it for 5 min in a similar manner to the samples prepared for the TEM images. Here it is observed that most of the coating is made of individual nanoparticles.…”
Section: Resultsmentioning
confidence: 94%
“…To demonstrate that the agglomeration is occurring on the fibers and not in the beam (as has been sometimes reported for this type of synthesis [ 47 , 48 ]), Figure 6 shows an SEM image of a lacy carbon TEM grid after passing the aerosol over it for 5 min in a similar manner to the samples prepared for the TEM images. Here it is observed that most of the coating is made of individual nanoparticles.…”
Section: Resultsmentioning
confidence: 94%
“…For the formation of Ag−Cu 3 P nanoparticle heterostructures, bimetallic Ag−Cu nanoparticles were generated in a spark ablation system, 55 and particles with a defined diameter of 30 nm were selected via an integrated filtering system for the deposition on a microelectromechanical systems (MEMS)-based heating chip for in situ TEM investigations. Subsequently, the chip was transferred to an ETEM with an integrated MOCVD system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A differential mobility analyzer system enabled the selection of sintered bimetallic nanoparticles with a diameter of 30 nm for the electrostatic deposition on MEMS-based heating chips. The parameters used for the synthesis and deposition of Ag–Cu nanoparticle heterostructures are in accordance with the parameters used in a recently published study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, spark ablation does not require a vacuum system and its electrical implementation is also simple, which facilitates scalable particle generation 22,23 . Moreover, due to the ability of periodically eroding two bulk electrodes with different compositions, spark ablation has utmost potential in the field of multielement NP synthesis with controllable composition and structure [24][25][26][27] . In the present paper we report on the spark ablation-based synthesis and characterization of Au/Co BNPs.…”
mentioning
confidence: 99%